What Is the Range of Current Teaching on Sanctification and What Ought a Wesleyan to Believe on this Doctrine? - Bounds, Christopher T. (The Asbury journal, 2007)
This article seeks to answer two questions: What is the range of teaching on sanctification in Protestantism and what ought a Wesleyan to believe on holiness? In response to the first question, we summarize the different positions on sanctification in the major theological traditions of Protestantism, beginning with the most optimistic views and ending with the most pessimistic. The similarities and differences among the major Christian traditions are brought to the fore, as well as the nuances of understanding among Wesleyan-Arminians. We seek to foster an appreciation for each tradition's understanding of holiness, while arguing for the need of the unique Wesleyan perspectives in evangelicalism.